2023
DOI: 10.1177/17568277231154204
|View full text |Cite
|
Sign up to set email alerts
|

Incompressible versus compressible large eddy simulation for the identification of premixed flame dynamics

Abstract: The present work compares the respective advantages and disadvantages of compressible and incompressible computational fluid dynamics (CFD) formulations when used for the estimation of the acoustic flame response. The flame transfer function of a turbulent premixed swirl-stabilized burner is determined by applying system identification (SI) to time series data extracted from large eddy simulation (LES). By analyzing the quality of the results, the present study shows that incompressible simulations exhibit sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The modeling effectively excluded acoustics from the governing equations without influencing the flame dynamics and prevented issues with self-excited or intrinsic thermoacoustic instability. This is justified as Eder et al [32] showed that even for a turbulent burner, both compressible and incompressible CFD configurations resulted in an identical FTF.…”
Section: Numerical Setupmentioning
confidence: 91%
“…The modeling effectively excluded acoustics from the governing equations without influencing the flame dynamics and prevented issues with self-excited or intrinsic thermoacoustic instability. This is justified as Eder et al [32] showed that even for a turbulent burner, both compressible and incompressible CFD configurations resulted in an identical FTF.…”
Section: Numerical Setupmentioning
confidence: 91%